A Numerical Method for Lane-Emden Equations Using Hybrid Functions and the Collocation Method - Changqing Yang; Jianhua Hou (Journal of Applied Mathematics)
A numerical method to solve Lane-Emden equations as singular initial value problems is presented in this work. This method is based on the replacement of unknown functions through a truncated series of hybrid of block-pulse functions and Chebyshev polynomials. The collocation method transforms the differential equation into a system of algebraic equations. It also has application in a wide area of differential equations. Corresponding numerical examples are presented to demonstrate the accuracy of the proposed method.